Synthesis, Characterization and Density Functional Study of LiMn1.5Ni 0.5O4 Electrode for Lithium ion Battery - M. Aruna Bharathi; K. Venkateswara Rao; M. Sushama (Журнал нано- та електронної фізики)
This paper analyses material issues of development of Li-ion batteries to store electrical energy. The performance of the battery is improved by developing the high energy density cathode materials at Nano level. This paper explains the synthesis of most interesting cathode material Lithium Manganese Spinel and its derivatives like transition metal oxide (LiNi0.5Mn1.5O4) using Co-Precipitation chemical method; it is one of the eco-friendly ,effective, economic and easy preparation method. The structural features of LiNi0.5Mn1.5O4 was characterized by XRD – analysis indicated that prepared sample mainly belong to cubic crystal form with Fd3m space group ,with lattice parameter a  8.265 and average crystal size of 31.59 nm and compared the experimental results with computation details from first principle computation methods with Quantum wise Atomistix Tool Kit (ATK),Virtual Nano Lab. First principle computation methods provide important role in emerging and optimizing this electrode material. In this study we present an overview of the computation approach aimed at building LiNi0.5Mn1.5O4 crystal as cathode for Lithium ion battery. We show each significant property can be related to the structural component in the material and can be computed from first principle. By direct comparison with experimental results, we assume to interpret that first principle computation can help to accelerate the design & development of LiNi0.5Mn1.5O4 as cathode material of lithium ion battery for energy storage.